Cytotoxic activity and selectivity index of binahong (Anredera cordifolia) extracts on MCF-7 breast cancer cells and vero normal cells line - Dita Sozianty; Rifki Febriansah (Indonesian Society for Biochemistry and Molecular Biology, 2020)
Background: Breast cancers occur because of an impaired balance between proliferation, differentiation, and apoptosis of breast glands. Natural products have potency as cytotoxic agents with less side effects than chemotherapy. One of the potential plants is Anredera cordifolia (Ten.) Stennis (binahong), which contains flavonoid 8-glucopyranosyl- 4’,5,7-trihydroxy flavone compounds. Objective: This study aims to determine the potency of binahong leaves extract as an anticancer for breast cancer in vitro and in silico. Methods: Preliminary tests using molecular docking of 8-glucopyranosyl-4’,5,7-trihydroxyflavone compounds on Bcl-2 and HER-2 proteins. The extraction and fractionation were to obtain binahong extract. Thin layer chromatography to identify flavonoid compounds in the extract. DPPH assay was performed to evaluate the antioxidant activity. MTT assay was performed to evaluate cytotoxic activity on MCF-7 breast cancer cells and Vero cells. Results: In silico test showed a stable bond between 8-glucopyranosyl- 4’,5,7-trihydroxylflavone, and Bcl-2 and HER-2 with a docking score of -7.5 kcal/mol and -8.0 kcal/mol, respectively. The binahong extract contain flavonoid compounds that had the retention factor value 0.78; 0.49; 0.35. Antioxidant test resulted IC50 value of 4940 μg/mL. Cytotoxic test resulted in IC50 value of 1073 μg/mL and 486 μg/mL for Vero cells and MCF-7 breast cancer cells, respectively. The comparison between IC50 produced a selectivity index value of 2.149, which shows that binahong extract was selective against MCF-7 breast cancers. Conclusion: This study concluded that binahong extract has weak potency as anticancer agent on MCF-7 cells.